Resective, Ablative and Radiosurgical Interventions for Drug Resistant Mesial Temporal Lobe Epilepsy: A Systematic Review and Meta-Analysis of Outcomes - Marathe, Kajol; Alim-Marvasti, Ali; Dahele, Karan; Xiao, Fenglai; Buck, Sarah; O'Keeffe, Aidan G.; Duncan, John S.; Vakharia, Vejay N. (Frontiers in Neurology, 2021)
1. Abstract 1.1. Objectives: One-third of individuals with focal epilepsy do not achieve seizure freedom despite best medical therapy. Mesial temporal lobe epilepsy (MTLE) is the most common form of drug resistant focal epilepsy. Surgery may lead to long-term seizure remission if the epileptogenic zone can be defined and safely removed or destroyed. We compare published outcomes following open surgical techniques, radiosurgery (SRS), laser interstitial thermal therapy (LITT) and radiofrequency ablation (RF-TC). 1.2. Methods: PRISMA systematic review was performed through structured searches of PubMed, Embase and Cochrane databases. Inclusion criteria encompassed studies of MTLE reporting seizure-free outcomes in >10 patients with >12 months follow-up. Due to variability in open surgical approaches, only comparative studies were included to minimize the risk of bias. Random effects meta-analysis was performed to calculate effects sizes and a pooled estimate of the probability of seizure freedom per person-year. A mixed effects linear regression model was performed to compare effect sizes between interventions. 1.3. Results: From 1801 screened articles, 41 articles were included in the quantitative analysis. Open surgery included anterior temporal lobe resection as well as transcortical and trans-sylvian selective amygdalohippocampectomy. The pooled seizure-free rate per person-year was 0.72 (95% CI 0.66-0.79) with trans-sylvian selective amygdalohippocampectomy, 0.59 (95% CI 0.53-0.65) with LITT, 0.70 (95% CI 0.64-0.77) with anterior temporal lobe resection, 0.60 (95% CI 0.49-0.73) with transcortical selective amygdalohippocampectomy, 0.38 (95% CI 0.14-1.00) with RF-TC and 0.50 (95% CI 0.34-0.73) with SRS. Follow up duration and study sizes were limited with LITT and RF-TC. A mixed-effects linear regression model suggest significant differences between interventions, with LITT, ATLR and SAH demonstrating the largest effects estimates and RF-TC the lowest. 1.4. Conclusions: Overall, novel ‘minimally invasive’ approaches are still comparatively less efficacious than open surgery. LITT shows promising seizure effectiveness, however follow-up durations are shorter for minimally invasive approaches so the durability of the outcomes cannot yet be assessed. Secondary outcome measures such as physical complications, neuropsychological outcome and interventional morbidity are poorly reported but are important considerations when deciding on first-line treatments.